2016
DOI: 10.18632/aging.100904
|View full text |Cite
|
Sign up to set email alerts
|

Telomere shortening leads to earlier age of onset in ALS mice

Abstract: Telomere shortening has been linked to a variety of neurodegenerative diseases. Recent evidence suggests that reduced telomerase expression results in shorter telomeres in leukocytes from sporadic patients with amyotrophic lateral sclerosis (ALS) compared with healthy controls. Here, we have characterized telomere length in microglia, astroglia and neurons in human post mortem brain tissue from ALS patients and healthy controls. Moreover, we studied the consequences of telomerase deletion in a genetic mouse mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 63 publications
3
23
0
Order By: Relevance
“…Telomerase-related DNA repair and transcription regulation may contribute to the survival of motor neurons in ALS (Singh et al, 2017 ). Surprisingly, Linkus et al ( 2016 ) found a trend of longer telomeres in microglia from human post-mortem brain tissue with ALS. However, knocking out telomerase in mice accelerated the ALS phenotype (Linkus et al, 2016 ).…”
Section: Telomerase and Diseases In The Central Nervous Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Telomerase-related DNA repair and transcription regulation may contribute to the survival of motor neurons in ALS (Singh et al, 2017 ). Surprisingly, Linkus et al ( 2016 ) found a trend of longer telomeres in microglia from human post-mortem brain tissue with ALS. However, knocking out telomerase in mice accelerated the ALS phenotype (Linkus et al, 2016 ).…”
Section: Telomerase and Diseases In The Central Nervous Systemmentioning
confidence: 99%
“…Surprisingly, Linkus et al ( 2016 ) found a trend of longer telomeres in microglia from human post-mortem brain tissue with ALS. However, knocking out telomerase in mice accelerated the ALS phenotype (Linkus et al, 2016 ). The longer telomeres in microglial cells may play a role in microglial proliferation, which contributes to ALS disease progression (Linkus et al, 2016 ).…”
Section: Telomerase and Diseases In The Central Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuronal cell death and synaptic loss results in the memory loss and other clinical findings in the dementias. Although not a dementia, a similar process may be relevant in other neurodegenerative diseases, such as amyotrophic lateral sclerosis (ALS) …”
Section: Part 2: Summary Of the Modelmentioning
confidence: 99%
“…Exposure to these and other environmental pathogens will accelerate neurodegeneration cascade, which will be accompanied by telomere shortening, a widely known determinant of cell senescence. Indeed, accelerated telomere shortening was observed in ALS mice ( 18 ) and in leukocytes from sporadic ALS patients ( 19 ). Telomere shortening in ALS certainly deserves more attention, since it may be modified by a healthy lifestyle ( 20 ).…”
Section: Age Factormentioning
confidence: 99%